Systematic review of pharmacokinetics and potential pharmacokinetic interactions of flavonolignans from silymarin - Tvrdý, Václav; Pourová, Jana; Jirkovský, Eduard; Křen, Vladimír; Valentová, Kateřina; Mladěnka, Přemysl (Medicinal research reviews, 2021)
Silymarin is an extract from the seeds (fruits) of Silybum marianum that contains flavonolignans and flavonoids. Although it is frequently used as a hepatoprotective agent, its application remains somewhat debatable, in particular, due to the low oral bioavailability of flavonolignans. Moreover, there are claims of its potential interactions with concomitantly used drugs. This review aims at a systematic summary and critical assessment of known information on the pharmacokinetics of particular silymarin flavonolignans. There are two known major reasons for poor systemic oral bioavailability of flavonolignans: (1) rapid conjugation in intestinal cells or the liver and (2) efflux of parent flavonolignans or formed conjugates back to the lumen of the gastrointestinal tract by intestinal cells and rapid excretion by the liver into the bile. The metabolism of phase I appears to play a minor role, in contrast to extensive conjugation and indeed the unconjugated flavonolignans reach low plasma levels after common doses. Only about 1%-5% of the administered dose is eliminated by the kidneys. Many in vitro studies tested the inhibitory potential of silymarin and its components toward different enzymes and transporters involved in the absorption, metabolism, and excretion of xenobiotics. In most cases, effective concentrations are too high to be relevant under real biological conditions. Most human studies showed no silymarin-drug interactions explainable by these suggested interferences. More interactions were found in animal studies, likely due to the much higher doses administered.
Keywords: Liver; Silybum marianum; játra; Antioxidants; absorption; silymarin; ostropestřec mariánský; Silymarin; flavonoidy; antioxidancia; Flavonoids; zvířata; Humans; interactions; excretion; metabolism; silybin; lidé; Animals